Greenbelts for pollution abatement : concepts, design, applications - Abbasi, S. A. (Shahid A.); Khan, Faisal I. (New Delhi : Discovery Pub. House, 2000)
With special reference to Pondicherry, India.
Includes bibliographical references (p. [235]-246).
Keywords: Windbreaks, shelterbelts, etc; Plants as sanitary agents; Air quality management; Greenbelts; Windbreaks, shelterbelts, etc. -- India -- Pondicherry; Plants as sanitary agents -- India -- Pondicherry; Air quality management -- India -- Pondicherry; Greenbelts -- India -- Pondicherry